Role of The Local Government in The Preservation Wadian Dadas of Ritual in The East Kalimantan Barito Regency of Central Province - Effrata Effrata; Tresia Kristiana (International Journal of Multi Discipline Science, 2018)
This research is about the role of local government in the effort to preserve the cultural customs that exist in the life of the Dayak people who Ma'anyan live in areas along the Barito river in East Barito regency. Wadian Dadas is one of the means of ceremonies in the field of traditional medicine in Ma'anyan Dayak tribe community in Central Kalimantan Province. That said, Wadian dadas originally Obtained through the inspiration Obtained by a woman named Ineh Ngundri Mountains. The woman is inspired to perform the duties of a god to heal a person or what is commanded by God. This woman is the first Wadian and is a messenger of gods embodied in the form of an eagle, then Wadian will be continued by the next Descendants. This study used descriptive qualitative method. Data collection techniques were conducted by primary and secondary collecting the data through interviews and observations with resource persons, for secondary Data Obtained from history books and documents belonging to the village government. The results Showed that Wadian Dadas originally for the healing rituals of the sick who started with the preparation of offerings, to perform the healing ritual by involving Wadian (shaman) is very trusted by the Dayak community Ma'anyan. Wadians in Ma'anyan Dayak community have now developed into Wadian Dadas Dances. Dadas Wadian dance begins with dances performed in the process of traditional medicine performed by Wadian. In the early 1980s Wadian dadas was known by some so that Wadian dadas the which originally served as a ritual ceremony medication Became an inspiration for the appearance of the dance Wadian Dadas. Dadas Wadian dance is one of the traditional dances. This dance is unique in its simple and energetic motion, the which has deep meaning and is Often presented in traditional events of Central Kalimantan. In the beginning this dance is performed with the excuse to get healed and free from evil spirits cause disease. The findings of this study are as the times progress, this dance is also presented at the event of welcoming and marriage. But there are still many people of Indonesia, even the citizens of Borneo who have not understood and are reluctant to desire to preserve this traditional dance. Dadas Wadian magical dance contains high value Because in every movement contains meaning, even in movement there is a spell pronunciation.